Antioxidant Enzyme Status in Human Cystic Echinococcosis - Yucebilgic, Guzide; Bilgin, Ramazan; Erbakan, Mustafa; S. Koltas, Ismail; K. Parsak, Cem (Asian Journal of Chemistry, 2010)
The objective of this study to investigate the role of antioxidant enzymes against toxic reactive oxygen species in human Hydatid disease (HD). This study took place in the Faculty of Medicine, University of Cukurova, Balcali Hospital in Adana, Turkey, from March 2004 to October 2005. The study was conducted on patients with cyctic echinococcosis (CE) before the surgical treatment and compared with healthy controls. Cyctic echinococcosis was determined by ELISA and western blotting method in serum samples. We assayed catalase (CAT) and superoxide dismutase activities (SOD) measured of 28 subjects and matched in 45 healthy controls. CAT and SOD activities of the patients and control group were found as 15.18 × 104 ± 3.25 × 104 IU/mg Hb, 2.40 ± 0.27 U/mL and 17.84 × 104 ± 2.61 × 104 IU/mg Hb, 3.63 ± 0.41 U/mL, respectively. Present results showed that there was a significant decrease in CAT (p < 0.05) and SOD (p < 0.001) activities of patients group as compared with that of the controls. There is an increase in oxidative stress in cystic echinococcosis. Despite this stress, the antioxidant system is deficient and adequate, in patients with cystic echinococcosis could be a defense system promotes the regulation and expression of these enzymes.